Overview of Depression Level in Elderly at The Welas Asih Nursing Home Tasikmalaya - Sandriani, Sandriani; Noviati, Elis; Srinayanti , Yanti; Abdurohman, Adit (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: Elderly is someone who has entered the age of 60 years and above and has entered the final stage of the life phase. This group categorised as elderly will occur a process called the aging process. Depression is one of the most common types of mental health disorders found in the elderly and the elderly have problems that are often faced by the elderly both physically and psychologically and affect about 7% of the world's elderly. Symptoms of depression show signs such as sadness, fatigue, sleep disturbances, decreased appetite and concentration, loss of interest and anhedonia, depression has become a major health problem with a significant global burden of disease. These problems increased especially during and after the covid-19 pandemic as a result of changing living conditions due to the need for isolation and social distancing. Objective To find out the description of the level of depression of the elderly at the Welas Asih Nursing Home in Tasikmalaya Regency. Method: This type of research uses descriptive with a quantitative approach with a quantitative descriptive research design. The population in this study were 35 elderly people. The sampling technique in this study was the Total Sampling technique, measuring the level of depression using the Geriatric Depression Scale (GDS) method by interviewing respondents using the GDS and measured using the GDS with 15 questions. Result: shows that the elderly with mild depression level were 14 respondents (46.7) while moderate/severe depression were 5 respondents (16.7). Conclusion: Showing that the elderly with the highest level of depression in the Welas Asih Tasikmalaya nursing home is a mild category of 14 people (4.7%), this age experiences many changes both physical, psychological, economic and spiritual which can affect the quality of life of an elderly person.